2023
DOI: 10.3389/fmed.2022.1089863
|View full text |Cite
|
Sign up to set email alerts
|

Case report:Multiple abscesses caused by Porphyromonas gingivalis diagnosed by metagenomic next-generation sequencing

Abstract: BackgroundExtraoral infection by Porphyromonas gingivalis (P. gingivalis) is extremely rare and challenging to diagnose because the fastidious pathogen is difficult to culture by traditional methods. We report the first case of a patient with multiple abscesses in muscles and the brain with dura empyema due to P. gingivalis, which was diagnosed by metagenomic next-generation sequencing (mNGS).Case presentationA 65-year-old male patient was admitted to our hospital for multiple lumps in his body. Brain magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This case study suggests that S. commune may cause granulomatous nasopharyngitis and surgical resection of the nodules, and subsequent medication with antifungal agents is the curative therapy for a captive cheetah. In this case, treatment with fluconazole was insufficient; in contrast, itraconazole exhibited a curative therapeutic effect, as suggested in previous studies [7,12,13]. However, the therapeutic effects of surgical treatment combined with antifungal medication remain unclear, and the relatively long-term remission of 73 days after fluconazole administration might have been due to the debulking of gross lesions.…”
supporting
confidence: 49%
See 2 more Smart Citations
“…This case study suggests that S. commune may cause granulomatous nasopharyngitis and surgical resection of the nodules, and subsequent medication with antifungal agents is the curative therapy for a captive cheetah. In this case, treatment with fluconazole was insufficient; in contrast, itraconazole exhibited a curative therapeutic effect, as suggested in previous studies [7,12,13]. However, the therapeutic effects of surgical treatment combined with antifungal medication remain unclear, and the relatively long-term remission of 73 days after fluconazole administration might have been due to the debulking of gross lesions.…”
supporting
confidence: 49%
“…The basidiomycete Schizophyllum commune is a common mushroom species that is isolated from various natural sources. However, it has been reported that the mushroom is occasionally responsible for infections in humans and animals [1,4,6,7,11,13]. In humans, S. commune infection has been reported as allergic bronchopulmonary mycosis, allergic fungal rhinosinusitis, and mucoid impaction of the bronchi [3,5,6,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In designing this study, we considered that although the cost of mNGS detection is higher than that of pathogen culture, its shorter turnaround time for results facilitates early initiation of targeted treatment ( 20 22 ), potentially leading to significant reductions in medical costs and improved patient prognosis, thereby combining cost-effectiveness. Nathan A. Pennell et al suggested that “the use of second-generation sequencing may expand the number of patients undergoing testing for common and less common genetic mutations, providing physicians and patients with more information to make informed and timely treatment decisions.…”
Section: Resultsmentioning
confidence: 99%
“…Other weapons in F. alocis’ arsenal include (1) the production of exotoxins, such as FtxA, which belongs to the RTX family and might help damage the surrounding cells by forming pores in the membranes of epithelial cells [ 13 ], (2) the ability to overcome oxidative stress thanks to enzymes such as superoxide reductase, which helps F. alocis to overcome the neutrophil response [ 14 ], and (3) the capability of mechanically adapting to the environment by forming pili-like projections [ 15 , 16 ]. To make things worse, and similar to other periodontopathogens such as Porphyromonas gingivalis , Fusobacterium nucleatum, and Aggregatibacter actinomycetemcomitans , F. alocis has also been detected in non-oral environments such as lung and brain abscesses [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%